Compensatory and Catalyzing Beliefs: Their Relationship to Pro-environmental Behavior and Behavioral Spillover in Seven Countries - Capstick, Stuart; Whitmarsh, Lorraine; Nash, Nick; Haggar, Paul; Lord, Josh (Frontiers in Psychology, 2019)
There is growing research interest in behavioral spillover and its potential for enabling more widespread lifestyle change than has typically been achieved through discrete behavioral interventions. There are some routes by which spillover could take place without conscious attention or explicit recognition of the connections between separate behaviors. However, in many cases there is an expectation that an individual will perceive behaviors to be conceptually related, specifically in terms of their compensatory (suppressing further action) or catalyzing (promoting further action) properties, as a prerequisite for both negative and positive spillover. Despite this, relatively little research has been carried out to assess the beliefs that may underpin spillover processes as held by individuals themselves, or to measure these directly. We develop and evaluate a survey-based instrument for this purpose, doing so in a sample of seven countries worldwide: Brazil, China, Denmark, India, Poland, South Africa, and the United Kingdom (approx. 1,000 respondents per country). This approach allows us to assess these measures and to compare findings between countries. As part of this, we consider the connections between beliefs about behavioral relationships, and other key variables such as pro-environmental identity and personal preferences. We observe higher levels of endorsement of compensatory beliefs than previous research, and even higher levels of endorsement of novel items assessing catalyzing beliefs. For the first time, we present evidence of the validity of such measures with respect to comparable constructs, and in relation to people’s consistency across different types of behaviors. We reflect on the implications of considering the relationships between behaviors in the context of people’s subjective beliefs and offer recommendations for developing this line of research in the broader context of spillover research and within a cross-cultural framework.